НОВІ НАДТВЕРДІ МАТЕРІАЛИ: ТЕОРІЯ І ЕКСПЕРИМЕНТ - Соколов, О. М. (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2019)
This article gives general overview of superhard and ultrahard materials, which include oxides, borides, nitrides carbon nitrides, cubic boron nitride (c-BN), diamond, et al. These materials are widely adopted in many industrial applications where high hardness, high incompressibility and sometimes chemical inertness and thermal stability are primary requirements. A review of the methods of theoretical calculations of the structure of the material and their experimental verification. It is concluded that, depending on the goals, when creating new superhard materials, it is necessary to use the following means for controlling the structure and properties of polycrystals: choosing compounds with a three-dimensional sp3 structure, short chemical bonds, high electron and valence bond density, and low ionicity of bonds, as well as using at high pressures of materials in the nanometric range). Together, this will make it possible to obtain superhard and ultrahard materials with a high level of heat resistance, strength and wear resistance, which allows it to be used to equip various types of tools.